2004
DOI: 10.1111/j.1532-5415.2004.52553.x
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorating Pain in Nursing Homes: A Collaborative Quality‐Improvement Project

Abstract: A multifaceted intervention improved pain-management process and outcome measures in nursing homes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
100
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(100 citation statements)
references
References 27 publications
0
100
0
Order By: Relevance
“…In one study, investigators reported that NH staff did not have enough specific knowledge to implement a targeted quality-improvement program completely and were reliant on external support (4). Other studies have shown that NH staff perceive quality-improvement initiatives as isolated projects rather than as an ongoing management style (42).…”
Section: Barriers To Improvementmentioning
confidence: 99%
See 1 more Smart Citation
“…In one study, investigators reported that NH staff did not have enough specific knowledge to implement a targeted quality-improvement program completely and were reliant on external support (4). Other studies have shown that NH staff perceive quality-improvement initiatives as isolated projects rather than as an ongoing management style (42).…”
Section: Barriers To Improvementmentioning
confidence: 99%
“…This occurrence is particularly unfortunate because CMS is the principal architect and funder of the Quality Improvement Organizations (QIOs). The main objective of the QIOs is to improve the quality of care provided to Medicare and Medicaid beneficiaries by working with health care providers on quality improvement efforts (4,72). Under the current regulatory framework, state NH inspectors play the role of cop, whereas QIO staff plays the role of quality consultant.…”
Section: The Regulatory Environmentmentioning
confidence: 99%
“…More recent studies have aimed to prompt organization-wide improvement in pain management through education, training, and support of nursing clinical leaders and clinical staff (primarily nursing) [40][41][42][43][44][45]. These studies have implemented multifaceted interventions, including some combination of pain management education and quality improvement methods, team building, and consultation and feedback by a pain management expert (usually a nurse).…”
Section: Best Practices In Pain Management In Persons With Dementiamentioning
confidence: 99%
“…Common organizational-level barriers cited included limited nurse/resident staffing ratios [42,46], high staff turnover [43,46], limited physician presence [46], and variable involvement of facility leadership [42]. Common clinical staff-level barriers included physicians' and nurses' beliefs about pain [42] and attitudes toward pain management (particularly concerns about use of pain medications) [43], physicians' and nurses' beliefs and attitudes about managing pain in patients with cognitive impairments [42], clinical staff's level of pain knowledge [41][42], and difficulties getting participation from all levels of key clinical staff [41][42]. For example, one study noted that facilities with lower staff turnover and the participation of key clinical leaders had improved pain management [40].…”
Section: Best Practices In Pain Management In Persons With Dementiamentioning
confidence: 99%
“…Whereas some studies find that participating organizations experience significant improvement relative to nonparticipants (e.g., Baier et al, 2004), others find no significant improvement (e.g., Landon et al, 2004) or find improvement on some measures, but not on others, relative to nonparticipants (e.g., Horbar et al, 2004). Studies that examine performance improvement across participants within collaboratives find similar variation, with some participants showing substantial improvement, whereas others in the same collaborative experience limited to no improvement (Lindenauer, 2008).…”
Section: Introductionmentioning
confidence: 99%